2020
DOI: 10.1002/jcp.30187
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐arrestin 2 mediates cardiac hypertrophy induced by thyroid hormones via AT1R

Abstract: We have previously reported that angiotensin II receptor type 1 (AT1R) contributes to the hypertrophic effects of thyroid hormones (TH) in cardiac cells. Even though evidence indicates crosstalks between TH and AT1R, the underlying mechanisms are poorly understood. Beta-arrestin (ARRB) signaling has been described as noncanonical signal transduction pathway that exerts important effects in the cardiovascular system through G-protein-coupled receptors, as AT1R. Herein, we investigated the contribution of ARRB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…Recently, it was reported that increased thyroid hormone activity is associated with AT 1 R-dependent cardiac hypertrophy. 49 The underlying mechanism suggests that β-arrestin-induced ERK signaling induced the hypertrophic effect as small interfering RNA-mediated ablation of β-arrestin-2 alleviated cardiac hypertrophy. Additionally, it has been noted that cardiac remodeling due to chronic Ang II exposure is mediated by the recruitment and internalization of β-arrestin-1 and L-type calcium channel, leading to a decrease in Ca 2+ flux.…”
Section: β-Arrestin Signaling and Biased Ligandsmentioning
confidence: 99%
“…Recently, it was reported that increased thyroid hormone activity is associated with AT 1 R-dependent cardiac hypertrophy. 49 The underlying mechanism suggests that β-arrestin-induced ERK signaling induced the hypertrophic effect as small interfering RNA-mediated ablation of β-arrestin-2 alleviated cardiac hypertrophy. Additionally, it has been noted that cardiac remodeling due to chronic Ang II exposure is mediated by the recruitment and internalization of β-arrestin-1 and L-type calcium channel, leading to a decrease in Ca 2+ flux.…”
Section: β-Arrestin Signaling and Biased Ligandsmentioning
confidence: 99%